The Factors Associated with Food Safety Practices on Food Handlers in Primary School Canteens - Suryani, Dyah; Sutomo, Adi Heru; Aman, Abu Tholib (Unnes Journal of Public Health, 2019)
Abstract Foodborne disease is one of the major health problems in the world wide as well as in Indonesia. Children are a group that is susceptible to this disease due to consuming unsafe foods because of their lack of knowledge. Unsafe food is identified from contamination of microorganism or chemical compounds. The purpose of this study was to determine the factors associated with food safety practices on food handlers in primary school canteens in Yogyakarta City. This research was conducted using an observational analytic study with cross sectional design. Samples in this study were 109 food handlers from 60 primary schools in Yogyakarta City. The research results showed that there was no association between gender (p=0.327), age (p=0.144), level of education (p=0.718), experience (0.220), training (p=0.180), level of knowledge (p=0.143) with food safety practices on food handlers. There was an association between attitude (p=0.031) with food safety practices on food handlers in primary school canteens in Yogyakarta City. Abstrak Penyakit bawaan makanan merupakan salah satu permasalahan kesehatan masyarakat di dunia maupun di Indonesia. Anak-anak merupakan kelompok yang rentan terhadap penyakit tersebut dikarenakan mengkonsumsi makanan yang tidak aman akibat ketidaktahuannya. Makanan tidak aman ditandai dengan kontaminasi mikroorganisme maupun senyawa kimia. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan praktek keamanan makanan pada penjamah makanan di kantin sekolah dasar wilayah Kota Yogyakarta. Penelitian ini merupakan penelitian observasional analitik dengan rancangan cross sectional. Sampel penelitian ini berjumlah 109 penjamah makanan dari 60 sekolah dasar di wilayah Kota Yogyakarta. Hasil penelitian menunjukkan bahwa tidak ada hubungan antara jenis kelamin (p=0,327), umur (p=0,144), tingkat pendidikan (p=0,718), pengalaman (0,220), pelatihan (p=0,180), tingkat pengetahuan (p=0,143) dengan praktek keamanan makanan pada penjamah makanan. Ada hubungan antara sikap (p=0,031) dengan praktek keamanan makanan pada penjamah makanan di kantin sekolah dasar wilayah Kota Yogyakarta.